Enabling technology for UDWDM access networks - Lamperski, Jan (Photonics Letters of Poland, 2009)
In the presented paper we show an original concept of technology for access networks with ultra dense channel multiplexing using a multifrequency translator with an acousto-optic frequency shifter as a key module. As an example of functional capabilities of this module, original experimental results of a multifrequency optical source based on an erbium-doped fiber ring configuration are presented. Optical frequency comb generation with a very stable 1,5 GHz and 2.5 GHz frequency separation was obtained. We also proposed original configurations which allow the realization of network devices for gigahertz spacing channel multiplexing such as optical multiplexers, demultiplexers and optical add/drop multiplexers. Full Text: PDF References: Jean-Pierre Laude, "DWDM fundamentals, components and applications", Artech House, (2002) Krzysztof Perlicki, "Systemy transmisji optycznej WDM", WKŁ, (2007) R. Sabella, P. Lugli, "Hihg Speed Optiacal Communications", Kluwer Academic Publisher, (1999) [CrossRef] D. M. Spirit, M. J. O?Machony, "High Capacity Optical Transmission Explained", John Wiley & Sons, (1995) "Dense wavelength division multiplexing techniques for high capacity and multiple access communications systems", IEEE J. Selest. Areas in Commun., 8 (1990) Elżbieta Bereś-Pawlik, "Elementy światłowodowe optycznych sieci telekomunikacyjnych", Oficyna Wydawnicza Politechniki Wrocławskiej, (2007) S. Yamashita et al,"Multiwavelength erbium-doped fibre laser using intracavity etalon and cooled by liquid nitrogen", Electron. Lett. 32, 1298 (1996) [CrossRef] A. Bellemare at al,"Room temperature multifrequency erbium-doped fiber lasers anchored on the ITU frequency grid", J. Lightwave Technol. 18, 825 (2000) [CrossRef] S. Kim et al,"Wideband multiwavelength erbium-doped fiber ring laser with frequency shifted feedback", Optics Commun. 190, 291 (2001) [CrossRef] P. Coppin et al,"Novel optical frequency comb synthesis using optical feedback", Electron. Lett. 26, 28 (1990) [CrossRef] J. Lamperski, Proc. Of 2nd Workshop on Fibre and Optical Passive Components, IEEE LEOS, Pavia. pp 253-258 (2000) J. Lamperski, IEEE Electronics Components & Technology Conference, Las Vegas, 2000 J. Lamperski et al, Proceedings SPIE 5952, Q-1 (2005) J. Lamperski, International Conference on Transparent Optical Networks ICTON, pp 282-285 (2008) J. Lamperski, A. Dobrogowski, P. Stepczak, OECC/ACOFT, P65 (2008) ITU-T Rec. G.692, (1998)